Mechanical properties of concrete containing ground palm oil fuel ash (POFA) as partial sand replacement - Nurul Atila, Mohd Salleh (2017)
The concrete production is high in our developing country. The demands for the natural sand were increasing day by day especially on developing countries, for instance, Malaysia. The natural sand which is needed for concrete has contribute a lot of environmental problems due to continuous sand mining from natural environment. Thus, researchers have been looking to find alternative ways to reduce the amount of sand used without sacrificing the strength. Palm Oil Fuel Ash (POFA) is a waste generated by the palm oil industry , which is a very big industry in Malaysia. That means the production of this waste is on a large scale Therefore, Palm oil fuel ash is seen as one of the alternative that can replace sand in concrete mixture production and could reduce the excessive production of palm oil fuel ash. The objective of this study is to investigate the effect of ground palm oil fuel ash as partial sand replacement on workability, compressive and flexural strength of concrete. Two mix were prepared in this research which are control mix and modified mix. Control mix were prepared with 0% of POFA. The modified mix consist various percentage palm oil fuel ash as partial sand replacement, which are in the range 10% to 40%. The cube specimens (100 x 100 x 100) mm and beam specimens (100 x 100 x 500)mm were casted and tested according to BS EN 12390-3:2002 and ASTM C78M (2005) for compressive and flexural strength. Before testing, all the specimens were subjected to water curing for 7, 14 and 28 days. The decreasing in slump value is due to high water absorption by POFA. As the POFA content increases, the slump value decreases. The concrete mix made using POFA as partial replacement of sand showed lower workability compared to normal concrete mixes. Finding shows that the test result exhibit that 10% of POFA replacement in concrete performed better performance compared to normal concrete both in compressive and flexural strength. It is the best recommended amount to be used as partial sand replacement to produced concrete with better strength. This study prove that ground POFA can be integrated as partial sand replacement in the production of concrete that can contribute to more sustainable environment.